2020
DOI: 10.1002/celc.202000931
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Benzazoles through Electrochemical Oxidative Cyclization Reactions

Abstract: An effective method for the synthesis of benzazoles through the electrochemical oxidative cyclization of o-aminophenol/oaminothiophenol/o-phenylenediamine and aldehydes was developed. A series of benzazoles were efficiently synthesized by using this method in good yields. Furthermore, this method was applied to the synthesis of the drug thiabendazole in a gram-scale reaction, which proved the practicality of the method. This approach avoids using catalysts and oxidants, and has the advantages of wide substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“… 15 Afterwards, as shown in pathway 1, 6a can readily react with 1a to obtain the imine D1, then imine D1 is converted to E1 which is oxidized (dehydrogenated) to afford the desired product 3aa via a radical-cation intermediate F1. 16 Similarly, hexagonal nitrogen-containing heterocyclic ring 6a also works well in the same way as shown in pathway 2. 17 …”
supporting
confidence: 53%
“… 15 Afterwards, as shown in pathway 1, 6a can readily react with 1a to obtain the imine D1, then imine D1 is converted to E1 which is oxidized (dehydrogenated) to afford the desired product 3aa via a radical-cation intermediate F1. 16 Similarly, hexagonal nitrogen-containing heterocyclic ring 6a also works well in the same way as shown in pathway 2. 17 …”
supporting
confidence: 53%
“…When the ratio of [EMIM]­BF 4 was increased or [EMIM]­BF 4 was used as the reaction solvent, the reaction yields all decreased (Table , entries 20–21). When the constant currents of the reaction were changed, the product yields dropped to 65% and 54%, respectively (Table , entries 21–22), which may be due to the side reaction . Therefore, the best suitable current for the system was the constant current of 6.0 mA.…”
Section: Results and Discussionmentioning
confidence: 99%
“…When CH 3 OH, THF, DMF, DMSO, DCE, and 22), which may be due to the side reaction. 46 Therefore, the best suitable current for the system was the constant current of 6.0 mA. In addition, we screened the reaction temperature and found that the yield of 3a was slightly decreased as the temperature increased (Table 1, entry 3 c ).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Organic electrosynthesis has been recognized as an environmentally friendly and enabling synthetic tool, in which electrons can be used instead of toxic or dangerous redox agents. [10] In these context, a variety of methodologies, such as electrochemical oxidative cyclization of o-aminothiophenol and aldehydes, [11] electrooxidative cyclization of benzylideneaminothiophenols, [12] electrochemical decarboxylative coupling of α-keto acids and 2-aminobenzenethiol, [13] electrochemical combination of aryl isothiocyanates with amines, [14] electrochemical cyclocondensation of alcohols and 2aminobenzenethiol, [15] and electrochemical oxidative cyclization of N-arylthioamides, [16][17][18] were developed for constructing benzothiazoles. However, it is noticed that the electrochemical synthesis of benzothiazoles by the reaction between ethers and 2-aminobenzenethiol has not been proposed until now.…”
Section: Introductionmentioning
confidence: 99%